TENDINITIS SUPRASPINATUS PADA IBU USIA 59 TAHUN : SEBUAH LAPORAN KASUS - YOSIE ARIEF SANJAYA; FERY LUVITA SARI; AGUS TAUFIQURROHMAN (LP2MTBM MAKARIOZ, 2022)
Shoulder injury is one of the most common injuries experienced during exercise other than knees and ankles. Inflammation of the tendons of the supraspinatus muscle causes supraspinatus tendinitis. In general, people with supraspinatus tendinitis have symptoms of shoulder pain. The presence of pain can interfere with sufferers in carrying out activities. Usually this pain will arise when doing activities. The patient of a Mother, Mrs EIS, aged 59 years, complained of difficulty and painful left shoulders when moved. Several times checked with a general practitioner, given painkillers, pain disappears when taken the drug but will arise again after the effect of the drug is exhausted. At the inspection, it seems asymmetrical, kenvy looks a little smaller. In palpation, pain when pressed on the tendons of the supraspinatus muscle. ROM of the shoulder joint experiences limitations of active motion in extension, abduction and external rotation. On special examination : Supraspinatus Tendinitis Test ( +), Apley Scratch Test ( +), Hawkings kennedy impingement Test (+).Injection of Lidocain 1% as much as 4 ml and Triamcinolon 40 mg with in plane ultrasound guidance to the supraspinatus tendon sheath. Patients feel better and more free. From the NRS pain score examination, 2 were obtained from before the management of the pain score 7 (NRS Pain Score maximum 10). Extension, abduction and external rotational movements are more flexible, with less muscle stiffness without being accompanied by pain.Furthermore, the patient is recommended to do physiotherapy to reduce muscle stiffness and eliminate the remaining limitations.Follow up this patient, it is recommended to do physiotherapy to reduce muscle stiffness and eliminate the remaining limitations,n : The supraspinatus muscle is one of the 4 relatively small rotator cuff muscles on the upper arm. Supraspinatus muscle is responsible for the motion of abduction. Some special examinations will further strengthen the establishment of the diagnosis.